Modelos Chain Ladder estocásticos y aplicaciones al cálculo de reservas en compañías de seguros - Mazuelos Vizcarra, Gisella Gabriela (2013)
This document is intented to deepen the study of univariate and multivariate Chain Ladder methods for estimating reserves in an insurance company. It presents from a theoretical and applicative perspective both the univariate deterministic and stochastic Chain Ladder methods. Although, the first is the most used method by insurance companies due to its simplicity and lack of probabilistic assumptions, the second, proposed by Mack (1993), allows the construction of confidence intervals for the estimated reserves, which is invaluable for researchers. We also develop the General Multivariate Chain Ladder model, which has the basic premise to analyze the possible relationship that may exist between different development triangles, thus providing another tool to improve inferences and predictions of reserves. These methods have been developed and applied to a database of 3 types of health insurance, thus showing the advantages and disadvantages of each of them in different scenarios and providing various tools for decision making in meeting the future obligations of insurance companies.